Renato Treves - Legal and political culture between Spain and Italy (Società e diritti, 2019)
This paper entitled "Renato Treves: Critical Illuminism and Sociology of Law" was published for the first time in the journal "Doxa. Quadernos de filosofía del derecho ”n. 12, 1992 (edited by the Centro de Estudios Constitucionales y la Universidad de Alicante), on the occasion of the death of Professor Renato Treves (1907-1992). Now we present with some or very few variations, this version for Italy many years later.Key words: sociology of law – Renato Treves - politics